The Role of Active Judges: A Comparative Study of Civil Cases and Administrative Disputes - Faridah, Siti; Hadiyantina, Shinta (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
The active role of judges is essential in ensuring the fair resolution of administrative and civil disputes. In the Administrative Court, judges are required to act under the dominus litis principle, which empowers them to take proactive steps in clarifying facts, guiding proceedings, and balancing the unequal positions between individuals and government authorities. This active role aims to uphold justice and protect citizens from administrative actions that violate legal norms or principles of good governance. In civil cases, by contrast, judges generally adopt a passive stance in accordance with the audi et alteram partem and party autonomy principles, although limited judicial intervention may still be necessary to safeguard fairness when power imbalances arise. This study employs a normative legal research method using statutory and conceptual approaches to examine the active judicial role's legal framework and theoretical justification. Drawing on theories of legal certainty, judicial activism, and due process of law, the study finds that while judicial activism is crucial to achieving substantive justice and transparency, it must operate within defined limits to preserve impartiality and procedural balance. Thus, the proper calibration of judicial activism serves not only to protect the integrity of the judicial process but also to ensure that justice remains both fair and effective in practice.